Plasmonic‐Enhanced Cholesteric Films: Coassembling Anisotropic Gold Nanorods with Cellulose Nanocrystals. Issue 9 (18th February 2019) - Cheng, Zheng; Ma, Yi; Yang, Lin; Cheng, Feng; Huang, Zhongjie; Natan, Avi; Li, Hongyan; Chen, Yong; Cao, Daxian; Huang, Zhifeng; Wang, YuHuang; Liu, Yongmin; et al.
Abstract: Incorporating photonic crystals with nanoplasmonic building blocks gives rise to novel optoelectronic properties that promise designing advanced multifunctional materials and electronics. Herein, the free‐standing chiral plasmonic composite films are designed by coassembling anisotropic plasmonic gold nanorods (GNRs) and rod‐like cellulose nanocrystals (CNCs). The effects of surface charge and concentration of the GNRs on the structure and optical properties of the CNC/GNR films are examined within this study. The CNC/GNR hybrid films retain the photonic characteristic of the CNCs host while concomitantly possessing the plasmonic resonance of GNRs. The negatively charged GNRs distribute uniformly in the layered CNCs host, inducing strong electrostatic repulsion among the CNCs and thus promoting the formation of a larger helical pitch than the case without GNRs. The positively charged GNRs decrease the chiroptical activity in the composite films with increasing the concentration of GNR, which is confirmed by the circular dichroism spectra. Notably, the surface plasmon resonances of GNRs enhance the fluorescence emission, which has been demonstrated by surface‐enhanced fluorescence signals in this work. This study sheds light on fabricating functional chiral plasmonic composite films with enhanced chiral plasmonics by utilizing CNCs as a dynamic chiral nematic template and adjusting surface charges. Abstract : In this work, free‐standing chiral plasmonic composite films are designed by coassembling anisotropic plasmonic gold nanorods (GNRs) and rod‐like cellulose nanocrystals (CNCs). The host–guest hybrid films exhibit tunable plasmonic optical properties including surface‐enhanced fluorescence and plasmon‐induced chiroptical activity. These interesting properties originate from the interaction of the photonic properties of the CNC matrix and plasmonic characteristics of GNRs.